Pengaruh Budaya Adaptif terhadap Kinerja Karyawan dengan Readiness For Change sebagai Variabel Mediasi (Studi pada Karyawan PT PLN Persero Unit Induk Distribusi Jawa Tengah dan DIY) - Dzakyul Fuaddy; Intan Ratna Wati (Faculty of Economics and Business Diponegoro University, 2025)
This study aims to analyze the influence of adaptive culture on employee performance, with readiness for change as a mediating variable, among employees of PT PLN (Persero) Central Java and Yogyakarta Distribution Main Unit.The research employs a quantitative approach, with data collected through questionnaires distributed to all employees who met the criteria using a census method. Out of a total population of 154 employees, 110 valid responses were obtained. The collected data were then analyzed using the Partial Least Squares (PLS) method with the assistance of SmartPLS software.The research results indicate that adaptive culture has a positive and significant effect on employee performance. Additionally, adaptive culture also has a positive and significant effect on readiness for change. Readiness for change itself has a positive and significant effect on employee performance. Furthermore, readiness for change is proven to mediate the relationship between adaptive culture and employee performance with a partial mediation level These findings confirm that adaptive culture plays a crucial role in improving employee performance, both directly and through readiness for change. Therefore, companies should strengthen their adaptive culture to enhance employees' readiness for change, ultimately leading to better performance outcomes.